Effects of liraglutide on weight, satiation, and gastric functions in obesity: a randomised, placebo-controlled pilot trial. (December 2017) - Halawi, Houssam; Khemani, Disha; Eckert, Deborah; O'Neill, Jessica; Kadouh, Hoda; Grothe, Karen; Clark, Matthew M; Burton, Duane D; Vella, Adrian; Acosta, Andres; Zinsmeister, Alan R; Camilleri, Michael
Summary: Background: Liraglutide, a long-acting GLP-1 receptor agonist, is approved for treatment of obesity; however, the mechanisms of action of liraglutide are incompletely understood. We compared effects of liraglutide versus placebo on gastric motor functions, satiation, satiety, and weight in obese individuals over 16 weeks. Methods: We did a randomised, double-blind, placebo-controlled pilot trial at a single centre (Mayo Clinic, Rochester, MN, USA). Participants were randomly allocated (1:1) by a computer generated randomisation schedule with no stratification to receive subcutaneous liraglutide (3·0 mg) or placebo, with standardised nutritional and behavioural counselling. Allocation was concealed from participants and study investigators. Otherwise healthy, local residents aged 18–65 years with body-mass index (BMI) 30 kg/m 2 or higher were included. Liraglutide or placebo was escalated by 0·6 mg/day each week for 5 weeks and continued until week 16. The primary outcome was change in gastric emptying (delay relative to baseline) of solids T1/2 (time taken for half the radiolabelled meal to empty from the stomach), measured at 5 weeks and 16 weeks in all patients who received at least one dose of study drug, with missing data imputed. Secondary outcomes included weight loss at weeks 5 and 16, satiation (volume to fullness and maximum tolerated volume), satiety, and fasting and postprandial gastric volumes at 16 weeks. This trial is registered withClinicalTrials.gov, numberNCT02647944, and is closed to new participants. Findings: Between Dec 18, 2015, and Sept 1, 2016, 40 adults were enrolled and randomly allocated (19 to the liraglutide group; 21 to the placebo group). Compared with placebo, liraglutide delayed gastric emptying of solids at 5 weeks (median 70 min [IQR 32 to 151] vs 4 min [–21 to 18]; p<0·0001) and 16 weeks (30·5 min [–11 to 54] vs −1 min [–19 to 7]; p=0·025). There was also significantly greater weight loss in the liraglutide group than in the placebo group (at 5 weeks: median 3·7 kg [IQR 2·8 to 4·8] vs 0·6 kg [–0·3 to 1·4], p<0·0001; at 16 weeks: 5·3 kg [5·2 to 6·8] vs 2·5 kg [0·1 to 4·2], p=0·0009). Satiation, as assessed by maximum tolerated volume at 16 weeks, was lower in the liraglutide group (median 750 mL [IQR 651 to 908]) compared with the placebo group (1126 mL [944–1185]; p=0·054). No significant differences were noted between groups in terms of volume to fullness, satiety, or fasting and postprandial gastric volumes at week 16. Post-hoc analysis showed that the T1/2 of gastric emptying of solids at 5 weeks correlated with change in weight loss at week 16 with liraglutide (Rs 0·567, p=0·018). Nausea was the most common adverse event in the liraglutide group (12 of 19) compared with placebo (four of 21). Interpretation: Effects of liraglutide on weight loss are associated with delay in gastric emptying of solids; measurement of gastric emptying (eg, at 5 weeks of treatment) may be a biomarker of responsiveness and may help to select individuals for prolonged treatment with this class of drug. Funding: US National Institutes of Health grant R56-DK67071.